Optimal Design of Water Distribution Network System by Genetic Algorithm in EPANET-MATLAB Toolkit - Hama, Burhan Hamza (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The emergence of computers in engineering applications increase the demand for improving the already available computer application tools for solving water distribution networks (WDNs). The demand is inevitable for both educational and practical purposes. In this thesis, the well-known computer application software EPANET is used in collaboration with MATLAB toolkit to optimize a water distribution network system given in the literature. In order to focus more on the practical aspects of computer application, and the resultant life cycle cost of a simple pipe network, a selected case study in northern part of Cyprus is analysed using these EPANET and MATLAB toolkits. The computer application tools are applied for the purpose of improving the methodology of water distribution network systems. This has been achieving by optimizing the design results of any network system. In order to minimize the diameter of the pipes (minimizing the cost) used in the water distribution network system an optimization model is carried out through genetic algorithm process coded in MATLAB. This was achieved while preserving the hydraulic design principles in balance. The model is limited for using the hydraulic design principles that is valid only for water as a liquid and circular cross-sectional shape of the pipes. The validity is tested through the water distribution network system of Hanoi city in Vietnam. The water distribution of this city was previously tested by other researches to achieve optimized solutions. Therefore, the results of this thesis got the opportunity to compare results with previous findings. As the validity is confirmed, the model is tested over Karaoğlanoğlu region in North Cyprus in order to select the best result for three different alternative scenarios. This is achieved by comparing the life cycle costs of the three scenarios. Although the basics of the implementation are sufficiently covered, the provided software and codes can be improved if life cycle cost analyses can be added to the EPANET- MATLAB toolkit.

ÖZ: Mühendislik uygulamalarında bilgisayar kullanımının artması ile birlikte, su dağıtım şebekeleri analizlerini gerçekleştirmek ve çözümlemek için mevcut bilgisayar uygulamalarının geliştirilmesine olan talebi artırmıştır. Bu talep hem eğitim ve hem de pratik amaçlar için kaçınılmazdır. Bu tez çalışmasında, EPANET adlı tanınmış bilgisayar yazılım uygulaması yardımı ile, literatürde daha önce birkaç kez optimize edilmeye çalışılan bir su dağıtım ağı sistemini optimize etmek için MATLAB araç seti ile birlikte kullanılmıştır. EPANET/MATLAB uygulamasının güvenirliği bu örnek üzerinden test edilmesinden sonra ise Kıbrıs'ın kuzeyindeki seçilmiş bir vaka incelemesi ile yakın zamanda uygulanan basit bir su şebekesinin analizleri optimize edilmiş ve pratikte uygulanan su şebekesinin maliyet analizleri karşılaştırılmıştır. Bu bağlamda su dağıtım şebeke sistemlerinin metodolojisinin geliştirilmesi amacıyla farklı iki yazılım programının birlikte çalışması sağlanmış ve bilgisayar uygulamaları yardımı ile verimli sonuçlar elde edilmiştir. Amaç uygulanan herhangi bir çalışmada bir ağ sisteminin tasarım sonuçlarını optimize ederek geliştirmektir. Su dağıtım şebekesi optimizasyon modelinde EPANET ile belirlenen boru çaplarını MATLAB'da kodlanmış genetik algoritma işlemi ile en aza indirgemek (maliyeti en aza indirmek) ana çalışma amacını oluşturmuştur. Bu, dengedeki hidrolik tasarım ilkelerini koruyarak başarılmıştır. Geliştirilen model yalnızca dairesel kesitli borular ve akışkan olarak ise “su” içeren durumlarda çalıştırılmak üzere sınırlandırılmıştır. Üzerinde çalışılan kombine analizin geçerliliği, Vietnam'daki Hanoi şehrinin su dağıtım şebekesi analizleri vasıtasıyla test edilmiştir. Bu şehrin su dağıtım sistemi daha önceleri optimize edilmiş ve bu çözümler güvenirliği artırmak amacı ile mevcut çalışma ile karşılaştırılmıştır. Bu nedenle, bu tezin sonuçları önceki bulgularla sonuçları karşılaştırma fırsatı yaratmıştır. Geçerlilik doğrulanırken, model üç farklı alternatif senaryonun en iyi sonucunu seçebilmek amacıyla Kıbrıs'taki Karaoğlanoğlu bölgesi üzerinde test edilmiştir. Bu, üç senaryonun yaşam döngüsü maliyetleri de ayrı ayrı incelenmiştir. Uygulamanın temelleri yeterince kapsanmış olmakla birlikte, yaşam döngüsü maliyet analizleri EPANET-MATLAB araç setine eklenebilirse sağlanan yazılımlar ve kodlar iyileştirilebilir.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2018. Supervisor: Assoc. Prof. Dr. Umut Türker.
Keywords: Civil Engineering; Water Distribution--Costs; Water-supply engineering; Water - Distribution - Mathematical models; EPANET-MATLAB Toolkit; Genetic Algorithm; Optimization; Water Distribution Network